Comparative Analysis of Thermal Decomposition Kinetics of Copolymers Based on Polyethylene Glycol Fumarate with Methacrylic Acid - Tuleuov, U.B.; Kazhmuratova, A.T.; Bolatbay, A.N.; Nassikhatuly, E.; Koishugulova, A.R. (Eurasian Journal of Chemistry, 2023)
The thermal properties of a copolymer based on polyethylene glycol fumarate with methacrylic acid in a ni-trogen atmosphere were studied in this paper. Four various heating rates and two types of a polyester resin composition were used. The analysis of thermal decomposition kinetics was implemented. Three kinetics methods namely Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose and Friedman were applied. Curves of a thermogravimetric analysis demonstrated that the thermal decomposition of copolymers with different molar ratios was observed. It was determined that the kinetic data depends on the studied copolymers’ composition. The obtained data showed a good convergence in various heating rates. Also, the thermodynamic characteris-tics were calculated namely the changes in the Gibbs energy (ΔG), enthalpy (ΔH) and entropy of activa-tion (ΔS). The Achar-Brindley-Sharp method was used to find the invariant kinetic parameters of decomposi-tion. Thus, the the kinetic compensation effect was applied to define a reaction model and a pre-exponential factor. A main phase of the copolymer decomposition in a narrow temperature range was determined. It was attested by a peak on the differential curve. An insignificant mass loss of the volatile-matter yield was ob-served in the range of 30–150 °C.
Keywords: dynamic thermogravimetry; thermal decomposition; copolymer based on polyethylene glycol fumarate with methacrylic acid; activation energy; isoconversional kinetic analysis